Classification of modern land management problems arising from the land reform - Ibatullin, S.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2020)
Discussions on fundamental concepts in land management have been and are ongoing throughout the land reform process. In such circumstances, domestic scientists have made considerable efforts to solve the problems of land management and land reform, beginning, first of all, with the systematization or classification of problems arising in the process of land reform or land management. The problems of interpretation of the concept of land management in Ukraine are investigated, based on the legislative support of land management, ways of carrying out and results of land reform and researches of domestic scientists. The analysis of problems that have arisen as a result of the implementation and incompleteness of land reform and which arise in the implementation of land management at the present stage and in previous years on the basis of a chronological analysis of scientific research. A scheme of classification of problems of land development is proposed, which includes problems of land management and problems of land reform. The analysis of the conformity of land management at different levels to the purpose of land management, which is fixed by regulatory legal acts, is carried out to date. The result of the conducted research and classification of the problems of land development will further be reflected in the deepening of the research on the specific problems of land management and the application of a systematic approach to their solution. Keywords: land management, land reform, land cadastre, land use purpose, sustainable land use.